Karakteristik Tanah Inceptisol yang Disawahkan di Kecamatan Indrapuri Kabupaten Aceh Besar - Teti Arabia; Manfarizah Manfarizah; Syakur Syakur; Bambang Irawan (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2018)
ABSTRACT This study aims to determine the soil characteristics of the Inceptisols which has been converted to paddy soils in Indrapuri Subdistrict, Aceh Besar District, using quantitative descriptive survey method. The results showed the morphological properties of rainfed rice fields and irrigated rice fields characterized by mottles Fe and Mn, in pedon BI1 found in all horizons (Ap, Bdg, Bg, Cg), in BI2 found in the horizon of Bdg, Bg, and BCg, while in the mixed garden (BI3) mottles is found only on the BCx horizon. In the plow pan layer (Bdg) rainfed rice fields and irrigated rice fields have a firm moist consistency, the wet is very sticky, while in the mixed garden is loose and rather sticky. The physical properties of soil at BI1, BI2 are characterized by the highest bulk density in the plow pan layer/Bdg (1.34 and 1.24 g.cm-3), slow and rather slow permeability (0.40 and 1.02 cm.jam-1), with lower porosity (38.01 and 42.15%) than BI3 horizon Bw1 (52.22%). Whereas at BI3 in the Bw1 horizon the lowest bulk density (1.18 g.cm-3), with moderate permeability (4.17 cm.hour-1). Soil chemical properties in BI1, BI2, and BI3 are classified as fertile with pH on Ap horizon 6.33 - 6.89 rather acid - neutral), Al dd is not measurable (very low), and CEC 24 - 36 cmol (+) kg-1 (medium - high). Keywords: soil characteristics, Inceptisols, irrigated paddy soils, paddy soils, mixed garden